PENGARUH AGROWISATA BALE TANI TERHADAP PENINGKATAN PEREKONOMIAN MASYARAKAT - Wahyuningsih, Roy (Jurnal Pendidikan Ekonomi (JURKAMI), 2024)
This research was motivated by the impact that the establishment of Bale Tani agrotourism had on the economic conditions of the surrounding community. This research aims to examine the increase in people's income as employees and traders in Bale Tani Agrotourism and examine the economic level of the community before and after the existence of Bale Tani Agrotourism in Banjaragung Village, Bareng District. This research uses quantitative methods. Data collection in this research used simple interviews, questionnaires and documentation. The population in this study was 54 employees and 13 traders who worked at Balai Tani Agrotourism. Researchers used saturated samples in selecting samples so that the sample size was 67 people. The data analysis techniques used in this research were descriptive tests, simple linear regression tests and partial t tests. The results obtained are that Bale Tani Agrotourism has a positive and significant effect on improving the community's economy. This means that the existence of Bale Tani Agrotourism in Banjaragung Village really helps improve the economy of the surrounding community